In vivo activity of the dual PI3Kδ and PI3Kγ inhibitor duvelisib against pediatric acute lymphoblastic leukemia xenografts - Randall, Joanna; Evans, Kathryn; Watts, Ben; Smith, Christopher M.; Hughes, Keira; Earley, Eric J.; Erickson, Stephen W.; Pachter, Jonathan A.; Teicher, Beverly A.; Smith, Malcolm A.; Lock, Richard B. (Pediatric blood & cancer, 2023)
Background Acute lymphoblastic leukemia (ALL) remains one of the most common causes of cancer‐related mortality in children. Phosphoinositide 3‐kinases (PI3Ks) are a family of lipid kinases, and aberrations in the PI3K pathway are associated with several hematological malignancies, including ALL. Duvelisib (Copiktra) is an orally available, small molecule dual inhibitor of PI3Kδ and PI3Kγ, that is Food and Drug Administration (FDA) approved for the treatment of relapsed/refractory chronic lymphocytic leukemia and small lymphocytic lymphoma. Here, we report the efficacy of duvelisib against a panel of pediatric ALL patient‐derived xenografts (PDXs). Procedures Thirty PDXs were selected for a single mouse trial based on PI3Kδ (PIK3CD) and PI3Kγ (PIK3CG) expression and mutational status. PDXs were grown orthotopically in NSG (NOD.Cg‐PrkdcscidIL2rgtm1Wjl/SzJAusb) mice, and engraftment was evaluated by enumerating the proportion of human versus mouse CD45+ cells (%huCD45+) in the peripheral blood. Treatment commenced when the %huCD45+ reached greater than or equal to 1%, and events were predefined as %huCD45+ greater than or equal to 25% or leukemia‐related morbidity. Duvelisib was administered per oral (50 mg/kg, twice daily for 28 days). Drug efficacy was assessed by event‐free survival and stringent objective response measures. Results PI3Kδ and PI3Kγ mRNA expression was significantly higher in B‐lineage than T‐lineage ALL PDXs (p‐values <.0001). Duvelisib was well‐tolerated and reduced leukemia cells in the peripheral blood in four PDXs, but with only one objective response. There was no obvious relationship between duvelisib efficacy and PI3Kδ or PI3Kγ expression or mutation status, nor was the in vivo response to duvelisib subtype dependent. Conclusions Duvelisib demonstrated limited in vivo activity against ALL PDXs.